PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KEPUASAN KERJA, INFORMASI KERJA YANG RELEVAN, DAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATING (Studi Empiris Pada SKPD Kabupaten Bintan) - Dian Erma Dewi; Yusrarlaini -; Devi Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect of budget participation on managerial performance with job satisfaction, job relevant information, and motivation to work as a moderating variable in SKPDs Bintan regency. The population in this study is the work units (SKPD) in Bintan regency government environment. The number of sectors in the district as much as 38 SKPDs Bintan consisting of 14 Department, 8 Agency, Office 1, 2 Secretariat, 1 General Hospital, 1 Inspectorate, 10 districts, and 1 Civil Service Police Unit. In this study were taken 26 SKPDs, the entire Department, Agency, Office, Hospital, Inspectorate, and the Civil Service Police Unit as a sample of 104 people. The research data collection using the method using a questionnaire survey. Analysis of the data in this study using the tools of SPSS software version 17. The results showed that the budgetary participation influence on managerial performance with job satisfaction, job relevant information, and motivation to work as a moderating variable.Keywords: Budgetary Participation, Job Satisfaction, Relevant Information, Motivation, and Managerial Performance.